1993
DOI: 10.1063/1.109735
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of thin films of TiO2 from Langmuir–Blodgett film precursors

Abstract: Excellent quality thin TiO2 films have been obtained by the thermal decomposition of n-octadecyl amine-titanyl oxalate complex multilayer Langmuir–Blodgett films. The films were characterized by x-ray diffraction and x-ray photoemission studies. X-ray diffraction studies suggest a preferred orientation of the TiO2 films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(27 citation statements)
references
References 14 publications
0
27
0
Order By: Relevance
“…The half band width was very small, which illustrated that the tin-containing compound was SnO 2 (22,24). In the region of 450-470 eV, the characteristic peaks of the 2 p transition of titanium at 458.6 and 464.3 eV confirmed that the Ti-containing compound was TiO 2 (2,24). In the O1s spectrum, the characteristic peak at 530.2 eV, which can be attributed to the lattice oxygen in SnO 2 and TiO 2 , was obtained (22).…”
Section: Formation and Characterization Of The Inorganic-inorganic Pementioning
confidence: 51%
See 3 more Smart Citations
“…The half band width was very small, which illustrated that the tin-containing compound was SnO 2 (22,24). In the region of 450-470 eV, the characteristic peaks of the 2 p transition of titanium at 458.6 and 464.3 eV confirmed that the Ti-containing compound was TiO 2 (2,24). In the O1s spectrum, the characteristic peak at 530.2 eV, which can be attributed to the lattice oxygen in SnO 2 and TiO 2 , was obtained (22).…”
Section: Formation and Characterization Of The Inorganic-inorganic Pementioning
confidence: 51%
“…1), all the nanoparticles were spheres and the mean size of the SnO 2 nanoparticles and TiO 2 nanoparticles in the organosol were 1.0 and 1.5 nm in diameter, respectively. The densities of the bulk phases were 6.95 g/cm 3 for SnO 2 and 3.80 g/cm 3 for TiO 2 . So the concentrations of nanoparticles in the spreading solutions could be calculated.…”
Section: Deposition Of the Alternate Nanoparticulate Multilayersmentioning
confidence: 99%
See 2 more Smart Citations
“…The TiO 2 particles in the colloidal dispersion at near-neutral pH were negatively charged, therefore cationic fi lm materials, particularly octadecylamine ODA , were used in these experiments. It has been shown that the use of long-chain amine monolayers and an aqueous subphase containing titanium potassium oxalate K 2 TiO C 2 O 4 2 ; TPO results in formation of a complex at the air-water interface 10 ; TiO 2 films are then obtained by LB deposition and post-heat-treatment 11 .…”
Section: Introductionmentioning
confidence: 99%